Risk of prostate cancer in low‐dose aspirin users: A retrospective cohort study. Issue 1 (15th March 2016) - Lapi, F.; Levi, M.; Simonetti, M.; Cancian, M.; Parretti, D.; Cricelli, I.; Sobrero, A.; Cricelli, C.
Abstract : A growing body of evidence indicates that use of low‐dose aspirin (LDA) reduces the risk of certain adenocarcinomas. While there are several and consistent findings on the protective effect of LDA on colorectal and other cancers, few and conflicting evidence is available on prostate cancer (PCa). The aim of this study was to assess whether LDA reduces the incidence rate of PCa. We conducted a nationwide, population‐based, retrospective cohort study by using Health Search IMS Health Longitudinal Patient Database (HSD). Patients with ischemic cardio‐ or cerebrovascular disease (index date) were identified. Time‐dependent multivariable Cox proportional hazard models were adopted to estimate Hazard Ratios (HRs) and related 95% confidence intervals (95% CI) of PCa associated with use of LDA. The exposure was lagged by one year to consider the latency of drug effect on the outcome onset. Within a cohort 13, 453 patients, the overall incidence rate of PCa was 2.5 per 1, 000 person‐years. Use of LDA was associated with a decreased incidence rate of PCa (HR = 0.64; 95% CI: 0.48–0.86), which was primarily driven by a frequency of LDA use equal to or higher than twice per week (HR = 0.60; 95% CI: 0.43–0.83). Such an association was more pronounced (HR = 0.43; 95% CI: 0.21–0.91) when LDA was used for five or more years. Our findings indicate that LDA use might be associated with a reduction of risk of PCa in patients with cardio‐ or cerebrovascular diseases. Abstract : What's new? Aspirin may reduce the risk of PCa, according to these new results. Previous work has shown that LDA, often prescribed for cardiovascular or cerebrovascular disease, reduces the incidence of colorectal cancer. To probe a possible connection with PCa, these authors undertook a large‐scale, population based retrospective cohort study involving more than 13, 000 participants. PCa struck less frequently among those taking LDA at least twice per week, particularly if they continued taking it for several years.